Aspects of memory in the sculptural work of Jane Alexander 1982-2009 - Nicol, Tracy-Lee (Rhodes University, Faculty of Humanities, Department of Fine Art, 2009)
Over three decades of research has shown that memories have significant effect on the behaviour, attitudes, beliefs, and identities of individuals and collectives, revealing also how experiences of trauma and acts of narrativisation have pertinence to the ways in which memories are stored and reconstructed. In this thesis a link is developed between memory, trauma, narrativisation processes and the interpretation of works by Jane Alexander, a contemporary artist whose work is informed by observations about South African life. Alexander's sculptures are revealed to be not only important vessels of collective memories and experiences, but also evocations of individuals' countermemories and traumas that remain unarticulated and invisible. Through an exploration of the workings of memory and its relation to her art, it is revealed how the past continues to exert its influence on many of South Africa's present sociopolitical concerns and interpersonal dynamics. Indeed constantly changing memories have a significant effect on future generations' perceptions of, and connectedness to, the past. While theories about memory have been deployed in Art History as well as the Humanities in general, Alexander's work has not previously been considered in light of the influence of these ideas. This thesis thus contributes a new dimension to literature on the artist.
Keywords: Alexander, Jane, 1959-; Collective memory -- South Africa; Memory in art; Women artists -- South Africa; Art, African -- Psychological aspects